Mathematical analysis for homoclinic bifurcation in a DC–DC converter with a photovoltaic module expressed by a piecewise‐linear characteristic. Issue 9 (28th June 2019) - Kousaka, Takuji; Osada, Shoma; Kato, Hideyuki; Asahara, Hiroyuki
Abstract: Homoclinic bifurcation is observed in DC–DC converters; this bifurcation may affect the qualitative characteristics of DC–DC converters with photovoltaic modules. However, no papers have reported the appearance of homoclinic bifurcation or have analyzed this phenomenon mathematically. As the first step toward understanding the dynamical mechanism, this article investigates homoclinic bifurcation in DC–DC converters with photovoltaic modules expressed by piecewise‐linear characteristics. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.